2023
DOI: 10.1111/joor.13573
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorders (TMD) in obesity patients: A systematic review and meta‐analysis

Giuseppe Minervini,
Rocco Franco,
Maria Maddalena Marrapodi
et al.

Abstract: ObjectiveObesity is a growing epidemic in the world. It increases the risk for severe health conditions, including diabetes, heart disease and stroke. Recent research has found that obesity is associated with an increased risk for temporomandibular disorders (TMDs). The purpose of this literature review with meta‐analysis is to analyse the possible association between obesity and temporomandibular disorders.Materials and MethodsPubmed, Web of Science and Lilacs were systematically searched until 01/03/2000. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Coinciding with our findings, Jordani et al demonstrated that painful TMDs exhibited a notable correlation with total body fat percentage, but in the multivariable analysis, obesity did not maintain its significance [64]. Two recent systematic reviews and meta-analyses did not show a clear association between obesity and TMDs and concluded that obesity is not a risk factor for TMDs [65,66].…”
Section: Discussionsupporting
confidence: 81%
“…Coinciding with our findings, Jordani et al demonstrated that painful TMDs exhibited a notable correlation with total body fat percentage, but in the multivariable analysis, obesity did not maintain its significance [64]. Two recent systematic reviews and meta-analyses did not show a clear association between obesity and TMDs and concluded that obesity is not a risk factor for TMDs [65,66].…”
Section: Discussionsupporting
confidence: 81%
“…Surgical interventions can result in substantial alterations in anatomy and functionality for patients, necessitating subsequent rehabilitation and ongoing pain management [ 78 , 79 ]. Employing precise surgical techniques can mitigate the severity of postoperative pain [ 80 , 81 ]. The careful handling of tissues, utilization of nerve- and vessel-sparing procedures, avoidance of tissue ischemia, and selection of non-muscle-splitting incisions collectively contribute to minimizing surgical pain and facilitating recovery [ 82 , 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Challenges arise due to the overlap of symptoms with other dental conditions and the variability in enamel defect presentations. The importance of a multidisciplinary approach, involving both gastroenterologists and dentists, becomes evident in navigating these diagnostic intricacies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%